Mengintegrasikan Hak Asasi Manusia dan Biosekuriti dalam Hukum Internasional: Menuju Kerangka yang Holistik - Noor Dzuhaidah Osman; Syahirah Abdul Shukor; Fareed Mohd Hassan; Nurfarhah Farhanim Shafie (Jurnal HAM, 2025)
Article 12 of the International Covenant on Economic, Social, and Cultural Rights (ICESCR) states the right to health as a fundamental human right. It emphasizes that healthcare should be available, accessible, acceptable, and of high quality for all individualsThe COVID-19 pandemic broadened the focus while highlighting the necessity of integrating biosecurity—including plant, animal, and human health—with a comprehensive One Health strategy within the framework of human rights.This doctrinal research examines key international agreements and organizations that govern biosecurity, biosafety, and the prohibition of biological weapons. It aims its integration with the right to health. The study finds that international public health and biosecurity regimes are fragmented, often leading to inconsistency in policy implementation  The major international agreements and institutions that control biosecurity, biosafety, and the ban on biological weapons are examined in this doctrinal study. It seeks to integrate the right to health. According to the findings, fragmented international public health and biosecurity regimes frequently result in inconsistent policy implementation. This article introduces a unified policy model that aligns biosecurity governance with the right to health, peace, and sustainable innovation. The integrative approach protects human health and biodiversity from a range of biological threats, offering new insights to the field.